Outcomes of placing short implants in the posterior mandible: A preliminary randomized controlled trial - Al-Hashedi, A.A.; Taiyeb-Ali, T.B.; Yunus, N. (Wiley, 2016)
Background Short dental implants can be an alternative to bone augmentation procedures at sites of reduced alveolar bone. Most studies on short implants are retrospective or multicentre reports that lack controlled and consistent comparison between different systems. This study aimed to compare clinical and radiographic outcomes of short implants in two different systems in the posterior mandible. Methods Twenty patients with two adjacent missing posterior teeth were recruited. Patients were assigned equally and randomly into two groups; Bicon® (6 or 8 mm) and Ankylos® (8 mm) implants. A two-stage surgical approach and single crowns were used for implant placement and loading. Outcomes included peri-implant clinical parameters, implant stability (Periotest values; PTVs) and peri-implant bone changes, which were assessed at baseline, 2, 6 and 12 months post-loading. Results No implant loss was encountered up to 12 months post-loading. No significant difference in the clinical or radiographic parameters was observed except for PTVs (p < 0.05) that was lower in Ankylos® implants. Conclusions The use of short dental implants was associated with excellent 12 months clinical and radiographic outcomes. Ankylos® and Bicon® implants demonstrated similar peri-implant soft tissue and alveolar bone changes. However, Ankylos® implants demonstrated better implant stability at all evaluation intervals.